2020
DOI: 10.3390/ijerph17249173
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Cultivation and Adolescent Psychopathology over Time-Mediation of Parent-Child Conflict

Abstract: Background: Concerted cultivation is a parenting strategy that parents nurture their children intensively by involving heavily in their children’s academic sphere as well as offering them different structured “enrichment” activities so that their children can succeed in the future competitive “rug rat race”. While this parenting strategy has been regarded as an effective strategy to promote child and adolescent development, it is deemed to create stress and anxiety for their children. The present study examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…In the future, qualitive studies can be implemented to further examine various forms of family conflicts and their effects on children's well-being. Fourth, similar to some studies on the same topic ( Grych et al, 1992 ; Leung, 2020 ), the conflict between parents and parent–child conflict in this study were both measured according to the reports of children. It is important to note that this self-report measure only reflects children's perception of family conflict and may not be objective enough.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the future, qualitive studies can be implemented to further examine various forms of family conflicts and their effects on children's well-being. Fourth, similar to some studies on the same topic ( Grych et al, 1992 ; Leung, 2020 ), the conflict between parents and parent–child conflict in this study were both measured according to the reports of children. It is important to note that this self-report measure only reflects children's perception of family conflict and may not be objective enough.…”
Section: Discussionmentioning
confidence: 90%
“…This finding was also consistent with previous studies ( Gunlicks-Stoessel et al, 2010 ; Tompson et al, 2015 ). For example, in a study on concerted cultivation in Hong Kong, Leung (2020) found that increased parent–child conflict was significantly related to increased depression and anxiety in children. The current study confirmed that parent–child conflict was a risk factor for children's depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents may resist parental intrusion by acting against their parents' wishes, which will generate parent-child conflict. A poorer parent-child relationship may in turn lead to poorer adolescent wellbeing [34].…”
Section: Overparenting Parent-child Conflict and Adolescent Anxietymentioning
confidence: 99%
“…Based on the existing overparenting literature e.g., [4] as well as the qualitative results of parents' and adolescents' focus groups on Chinese overparenting [11], the 42-item PCOS/MCOS were developed with eight dimensions: parental surveillance, parental intrusion into children's routines and direction, over-emphasis on children's school performance, repeated comparisons of children's achievements with other children's, over-scheduling of tutorials and talent enhancement classes, anticipatory problem-solving, excessive care, and disproportionate affective involvement [58]. Over-emphasis on children's school performance and over-scheduling of tutorials and talent enhancement classes are regarded as unique features of concerted cultivation specific to Chinese parenting practice [34]. A sample item reads "I need to report everything to my father/mother" Respondents rated each item on a 6-point Likert scale (1 = "strongly disagree"; 6 = "strongly agree").…”
Section: Instruments 221 Overparentingmentioning
confidence: 99%